BIMBINGAN BAGI ANAK CERDAS DAN BERBAKAT DI KELAS VI SD GMIT 03 KALABAHI - Novi Greace Makena; Rani Puspa Atakama, Noni Wulandewi Maulau, Obetnego Kamalau, Petrus Mau Tellu Dony, Yessy Mata, Nehe (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
This study aims to examine the importance of appropriate guidance for gifted and talented children in optimizing their overall development potential. Children with exceptional intelligence and talent have special needs that cannot always be met through a general educational approach. Through a literature review of various theories and research findings since 2015, this article explores the characteristics of gifted and talented children, the challenges they face, and effective guidance strategies. Studies show that gifted children are vulnerable to emotional, social, and academic problems if they do not receive adequate support. Therefore, guidance and counseling services play a crucial role in helping them adjust, manage their emotions, and optimally develop their potential. This research recommends the development of individualized, collaborative, and needs-based guidance programs for gifted and talented students. With the right approach, intelligent and gifted children can grow into high-achieving individuals with balanced personalities.